THEORIES OF VALUE AND THE PROBLEM OF THE INTEGRITY OF THE INDIVIDUAL'S WORLDVIEW (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the relationship between value theories and the personality worldview, as well as their differences and features. An individual's worldview is shaped by his life experience, social and cultural factors, while values are regarded as the main factor determining these views. The article examines the variability of values and an individual's worldview in relation to social and cultural processes occurring in society. This research contributes to a deeper understanding of the complex relationships between an individual and society.